IMPERATIVE OF ENVIRONMENT PRESERVATION AMIDST WARFARE: NAVIGATING CONTRIBUTION INTO THE EQUATION OF SAFEGUARDING FIRST AND SECOND GENERATION HUMAN RIGHTS - Sumaiya Sultana Ritu (UCL Journal of Law and Jurisprudence, 2024)
Environmental destruction and resource depletion during armed conflicts are unfortunately widespread. Pollution, deforestation, and habitat degradation following war can have long-term environmental repercussions. Despite the proliferation of various international conventions and treaties specifically designed to protect the well-being of civilians, combatants, and other vulnerable individuals affected by armed conflicts, it is evident that the preservation of the environment has not been accorded commensurate priority. The research examines environmental neglect and resource depletion during conflicts in light of humanitarian and human rights concerns. This paper comprehensively examines the multifaceted mechanisms by which environments are detrimentally impacted during times of conflict. Moreover, it established a compelling correlation between these destructive processes and the severe infringement upon human rights, specifically in terms of the deprivation of essential resources necessary for individuals to lead a dignified and sustainable post-war existence, as well as exploring potential solutions and offering recommendations to foster a sustainable future.
Keywords: Environment preservation; Warfare; Human rights; Humanitarian law; Environment Destruction.